Effective connectivity underlying neural and behavioral components of prism adaptation - Schintu, Selene; Gotts, Stephen J.; Freedberg, Michael; Shomstein, Sarah; Wassermann, Eric M. (Frontiers in Psychology, 2022)
Prism adaptation (PA) is a form of visuomotor training that produces both sensorimotor and cognitive aftereffects depending on the direction of the visual displacement. Recently, a neural framework explaining both types of PA-induced aftereffects has been proposed, but direct evidence for it is lacking. We employed Structural Equation Modelling (SEM), a form of effective connectivity analysis, to establish directionality among connected nodes of the brain network thought to subserve PA. The findings reveal two distinct network branches: 1) a loop involving connections from the parietal cortices to the right parahippocampal gyrus, and 2) a branch linking the lateral premotor cortex to the parahippocampal gyrus via the cerebellum. Like the sensorimotor aftereffects, the first branch exhibited qualitatively different modulations for left versus right PA, and critically, changes in these connections were correlated with the magnitude of the sensorimotor aftereffects. Like the cognitive aftereffects, changes in the second branch were qualitatively similar for left and right PA, with greater change for left PA and a trend correlation with cognitive aftereffects. These results provide direct evidence that PA is supported by two functionally distinct subnetworks, a parietal-temporal network responsible for sensorimotor aftereffects and a frontocerebellar network responsible for cognitive aftereffects.